Isolation, characterization, activity test and molecular identification of thermophilic bacteria producing proteases from Dolok Tinggi Raja Natural Hot Springs, North Sumatra, Indonesia - Edy Fachrial; VISENSIUS KRISDIANILO; Harmileni HARMILENI; I Nyoman Ehrich Lister; Titania T Nugroho; Saryono SARYONO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fachrial E, Krisdianilo V, Harmileni, Lister INE, Nugroho TT, Saryono. 2021. Isolation, characterization, activity test and molecular identification of thermophilic bacteria producing proteases from Dolok Tinggi Raja Natural Hot Springs, North Sumatra, Indonesia. Biodiversitas 22: 1725-1732. Proteases are complex enzymes that can be applied in both commercial products and physiological fields. This enzyme accelerates the breakdown of peptide bonds in polypeptides and proteins using hydrolysis reactions, transforming them into simpler bonds. In recent years, the demand for protease enzymes in Indonesia is still dependent on imported products, and there has also been an increase in their use. This is because there are many advantages in terms of efficiency, environmental friendliness, and its ability to catalyze a reaction without by-products. Proteases dominate the enzyme market with a total of 70% sales. Furthermore, they are manufactured from thermophilic bacteria as a solution to the problem of enzyme use in industries, where enzymes are easily damaged at high temperatures. The thermophilic protease enzyme can be found in thermophilic microorganisms living in extreme temperatures such as hot springs. There are lots of mountainous areas in North Sumatra Province, Indonesia with many hot springs. For example, the Dolok Tinggi Raja Natural Hot Springs of Simalungun District which has a water temperature of 50oC with a pH of about 6, the potential of which still needs to be explored. This study aims to isolate and determine the activity and molecular structure of thermophilic bacteria producing protease in Dolok Tinggi Raja Natural Hot Springs. Protease activity was determined based on the formation of clear zones in Skim Milk Agar medium. In addition, a total of 20 isolates were successfully obtained from sediment and water. Each was tested biochemically and morphologically, where 19 isolates had the activity of proteases, with the highest in isolate UTMTR VK S9 of 23.67 U/mL. Molecular identification was performed by the amplification of 16SrRNA gene based on BLAST and phylogenic analysis with MEGA X. Phylogenic results showed that isolate UTMTR VK S9 possessed similarities to Bacillus paralicheniformis strain A30103. Meanwhile, more research is required to purify enzymes for application in the industrial world.